[SOLVED] -1*-1=1 ? how to prove 1. The problem statement, all variables and given/known data Well as the subject states..how does one prove that -1*-1=1? I think you have to use proof by contradiction but I dont know what to do after assuming that it is not true.
Ok I think I got it...I was told that I should start by knowing that 0*0=0 and that 1-1=0 such that 0*0=0 => (-1+1)*(-1+1)=(-1*-1)-1-1+1=0 (-1*-1)-1=0 and so -1*-1=1
Well, think about what you know about (-1). Then, think about what you know about (0). More specifically, note: 0 = (1 + (-1)) and 0 = ((-1)+1) AND 0 = 0*0. You should be able to get the algebraic proof from there. EDIT: Dang, you got it already. Good job, but don't double post, just edit your original post.